Cultural and Intercultural Competence in Translation: State or the art - Gregorio Cano, Ana (Íkala, Revista de Lenguaje y Cultura, 2012)
In this paper, I will analyse the theoretical framework of the cultural and intercultural competence in translation through the review of literature in the field. Furthermore, I will describe some definitions of culture with applicable aspects for the design of a future proposal of cultural and intercultural competence model in translation. Conclusions suggest the need for more empirical studies regarding the role/acquisition of cultural and intercultural competence as training programmes and teaching and learning activities are currently mainly based on theoretical notions. <!-- [if gte mso 9]> <![endif][if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]-->